Effect of PSB and VAM with different Sources of Phosphatic Fertilizer on Growth Attributes, Chlorophyll Content and Yield of Wheat - Banerjee, Mahua; Rai, R. K.; Maiti, Debtanu (International Journal of Bio-resource and Stress Management, 2023)
Field experiments were conducted during rabi seasons of 2002-03 and 2003-04 at Indian Agricultural Research Institute, New Delhi to see the response of various phosphatic sources in the form of chemical fertilizers and biofertilizers on growth attributes, chlorophyll content and yield of wheat (cv. HD 2285). The experimental design of the field experiment was randomized block design. There were twelve treatments where various phosphatic sources were applied either singly or in combination with nitrogen. All these treatments were replicated thrice. The treatment N120SSP30VAM recorded highest leaf area of 224.57 cm2 plant-1 at late jointing stage in 2002-03 while in 2003- 04 the leaf area of N120RP30PSB (230.57 cm2 plant-1) was highest. In both the years, the treatments N120SSP30VAM and N120RP30PSB gave statistically at par values for dry matter yield which were higher than all other treatments. At late jointing stage, the highest chlorophyll content of 2.86 mg g-1 fresh weight and 2.95 mg g-1 fresh weight were observed in N120SSP30VAM in 2002-03 and in N120RP30VAM in 2003-04 respectively and during both the years the values were statistically at par. Due to better leaf area, dry matter and chlorophyll content, the treatments N120SSP30VAM and N120RP30PSB also resulted in higher grain yield, stover yield and harvest index. Thus combined application of VAM with SSP and PSB with RP can give satisfactory growth as well as yield in case of wheat.